Metformin Improves Epithelial-to-Mesenchymal Transition Induced by TGF-β1 in Renal Tubular Epithelial NRK-52E Cells via Inhibiting Egr-1 - Meiping Guan; Wenqi Li; Lingling Xu; Yanmei Zeng; Dan Wang; Zongji Zheng; Fuping Lyv; Yaoming Xue (Journal of Diabetes Research)
The early growth response- (Egr-) 1 has been found to play a key role in organ fibrosis. Metformin has been shown to be effective in attenuating renal tubular epithelial-to-mesenchymal transition (EMT), which is involved in renal fibrosis. However, it is unknown whether metformin improves EMT via inhibiting Egr-1. In this study, rat renal tubular epithelial (NRK-52 E) cells, treated by transforming growth factor- (TGF-) β1 of 10 ng/ml with or without metformin of 1 mmol/l, were transfected by siEgr-1 or M61-Egr-1 plasmids to knock down or overexpress Egr-1, respectively. The gene and protein expressions of E-cadherin, α-SMA, fibronectin (FN), and Egr-1 were determined by real-time quantitative PCR and Western blotting, respectively. We observed that TGF-β1 significantly reduced E-cadherin expression and upregulated the expressions of FN, α-SMA, and Egr-1, which can be reversed by metformin. M61-Egr-1 transfection could exacerbate EMT, which can be reversed by metformin. Taken together, our data show that Egr-1 plays an important role in TGF-β1-induced EMT of renal tubular epithelial cells and metformin improves EMT while inhibiting Egr-1, which provides a potential novel target to combat renal fibrosis.